Archives, ancestors, practices : archaeology in the light of its history - Schlanger, Nathan; Nordbladh, Jarl (Berghahn Books, 2008)
In line with the resurgence of interest in the history of archaeology manifested over the past decade, this volume aims to highlight state-of-the art research across several topics and areas, and to stimulate new approaches and studies in the field. With their shared historiographical commitment, the authors, leading scholars and emerging researchers, draw from a wide range of case studies to address major themes such as historical sources and methods; questions of archaeological practices and the practical aspects of knowledge production; 'visualizing archaeology' and the multiple roles of ic.